Three-dimensional Seismic Attenuation Tomography Imaging for Guntur Volcano Using Spectral Ratio Method - JAYANTI PUSPASARI (NIM 12404001), TREVI
Medium characterization could be defined by physical parameters such as seismic velocity and attenuation. In the study of seismic attenuation tomography the amplitude and travel time of P-wave and S-wave have been used to image the 3-D internal structure of a volcano. The object of this research is Guntur volcano which is one of active volcanos in West Java. The study area covers a volume of 20x20x20 km3 with a block size of 2x2x2 km3. Base on seismogram data hypocenter positions have been determined by applying three circles intersection method followed by a grid search method. The Least Square (LSQR) inversion method has been used to process the velocity and attenuation inversions. The input data for the velocity inversion are delay time (dt) defined as the difference between the travel time of seismic wave in the Earth and that calculated in the reference velocity model. The input for seismic attenuation inversion is differential attenuation (.tsp*) resulting from spectral ratio calculation. The distribution of hypocenters is concentrated at the depth interval of 1-6 km from Guntur’s surface. Seismic velocity and attenuation tomograms indicate a consistency of negative velocity anomaly and high attenuation zones beneath the Guntur summit, Gandapura caldera, and Kamojang caldera. Furthermore, this zone is interpreted as a hot material zone, which may be associated with the magma chamber.